A Review on Multifunctional Epoxy-Based Joncryl® ADR Chain Extended Thermoplastics. (27th April 2022) - Standau, Tobias; Nofar, Mohammadreza; Dörr, Dominik; Ruckdäschel, Holger; Altstädt, Volker
Abstract: Reactive additives allow to adapt the properties of thermoplastic polymers during processing and for their later use. The chemical modification using multifunctional epoxide styrene-acrylic chain extenders (CE) in reactive processes is by now an established method to prevent degradation and to improve the process ability as well as the final properties of thermoplastics. One of the most common representatives of these CE is better known under its trade name Joncryl®. Since several years ago, Joncryl® ADR owes an ever-growing importance in industry and academia. It can be applied as reactive melt modifier for numerous polymers, mainly polyesters, where it largely affects the rheological properties and the thermal behavior. This review focuses on the reactive behavior of Joncryl® ADR as well as the induced changes in the rheological behavior of the polymers caused by this modification. The Joncryl® ADR incorporation leads to an increased shear viscosity, a higher melt strength and induces strain hardening due to the formation of branched chains and/or even crosslinking. The crystallization is also directly influenced by the changed chain topology. Eventually, this review article extensively addresses the benefits of using Joncryl® for processing such as stabilization, recycling, foaming, and polymer blending. Graphical Abstract: UF0001